اﻹﺗﺠﺎه اﻟﻤﻨﻄﻘﻲ ﻓﻲ اﻟﺘﺄوﯾﻞ وأﺛﺮه ﻓﻲ إزاﻟﺔ اﻟﻠﺒﺲ ﻋﻦ اﻟﻜﻼم ﻋﻨﺪ أھﻞ اﻟﻌﺪل واﻟﺘﻮﺣﯿﺪ (Journal of the College of Education for Women, 2019)
The exegesis of the underpinnings adopted Isolationists to prove their beliefs, and a confirmation of their dogmatic ideas, as it depends mentality dimensions exegesis and logical cited as confirms Isolationists discharge verses Confusables in the Koran that are incompatible with their dogmatic origins. The interpretation of the text needs a deeper denote movement stresses the mind and influence in guiding the text by catalysing the mind to get to the diligence who leads to the desired meaning, and remains the owners of Justice and uniformity vision of creation the divine instantly or future. Isolationists exegesis who is based on reason and logic, who set off him for the disposal of verses and hadiths that phenomena indicate that God is in sky, and enters the exegesis and the language of the Koran as metaphorically enters the general language.